Recent Progress in Developing Extracellular Vesicles as Nanovehicles to Deliver Carbohydrate-Based Therapeutics and Vaccines - Japigorn Puagsopa; Niksa Tongviseskul; Thapakorn Jaroentomeechai; Bunyarit Meksiriporn (My University, 2025)
Cell-derived, nanoscale extracellular vesicles (EVs) have emerged as promising tools in diagnostic, therapeutic, and vaccine applications. Their unique properties including the capability to encapsulate diverse molecular cargo as well as the versatility in surface functionalization make them ideal candidates for safe and effective vehicles to deliver a range of biomolecules including gene editing cassettes, therapeutic proteins, glycans, and glycoconjugate vaccines. In this review, we discuss recent advances in the development of EVs derived from mammalian and bacterial cells for use in a delivery of carbohydrate-based protein therapeutics and vaccines. We highlight key innovations in EVs’ molecular design, characterization, and deployment for treating diseases including Alzheimer’s disease, infectious diseases, and cancers. We discuss challenges for their clinical translation and provide perspectives for future development of EVs within biopharmaceutical research and the clinical translation landscape.
Keywords: Biopharmaceutical; Extracellular Vesicles; Glycoconjugate; Extracellular vesicles in disease